2011
DOI: 10.1103/physrevb.83.195434
|View full text |Cite
|
Sign up to set email alerts
|

Transport in superlattices on single-layer graphene

Abstract: We study transport in undoped graphene in the presence of a superlattice potential both within a simple continuum model and using numerical tight-binding calculations. The continuum model demonstrates that the conductivity of the system is primarily impacted by the velocity anisotropy that the Dirac points of graphene develop due to the potential. For one-dimensional superlattice potentials, new Dirac points may be generated, and the resulting conductivities can be approximately described by the anisotropic co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
92
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(96 citation statements)
references
References 55 publications
4
92
0
Order By: Relevance
“…Recently, a number of theoretical studies predicted that the chiral nature of charge carriers results in highly anisotropic behaviours of massless Dirac fermions in graphene under periodic potentials and generates new Dirac points at energies E SD = ±ћν F |G|/2 in graphene superlattice (here ν F is the Fermi velocity of graphene and G is the reciprocal superlattice vector) [13][14][15][16]. Despite these suggestive findings [13][14][15][16] and many other interesting physics [17][18][19][20][21][22] in graphene superlattice, the experimental study of this system is scarce due to the difficulty in fabricating graphene under nano-scale periodic potentials [23]. Until recently, it was demonstrated that graphene superlattice (corrugated graphene or moiré pattern) induced between the top graphene layer and the substrate (or the underlayer graphene) acts as a weak periodic potential, which generates superlattice Dirac points at an energy determined by the period of the potential [24][25][26].…”
mentioning
confidence: 99%
“…Recently, a number of theoretical studies predicted that the chiral nature of charge carriers results in highly anisotropic behaviours of massless Dirac fermions in graphene under periodic potentials and generates new Dirac points at energies E SD = ±ћν F |G|/2 in graphene superlattice (here ν F is the Fermi velocity of graphene and G is the reciprocal superlattice vector) [13][14][15][16]. Despite these suggestive findings [13][14][15][16] and many other interesting physics [17][18][19][20][21][22] in graphene superlattice, the experimental study of this system is scarce due to the difficulty in fabricating graphene under nano-scale periodic potentials [23]. Until recently, it was demonstrated that graphene superlattice (corrugated graphene or moiré pattern) induced between the top graphene layer and the substrate (or the underlayer graphene) acts as a weak periodic potential, which generates superlattice Dirac points at an energy determined by the period of the potential [24][25][26].…”
mentioning
confidence: 99%
“…The advent of graphene has rapidly sparked interest in its superlattices, too [13][14][15][16][17][18][19][20][21][22] . The principal novelty in this case is the Dirac-like spectrum and the fact that charge carriers are not buried deep under the surface, allowing a relatively strong superlattice potential on a true nanometer scale.…”
mentioning
confidence: 99%
“…These semiconductor NDR systems can also show interesting phenomena, such as intrinsic bistability due to charge accumulation 14 . Pursuing the recent interest in graphene superlattices transport and thermal properties [15][16][17][18][19][20][21][22][23][24] , it is a natural question to ask whether a graphene superlattice could exhibit similar features.…”
mentioning
confidence: 99%